Decoded - Mohd Zulkifly, Muhammad Zuraidi; Mohd Amini, Amin Faris; Amat Jufri, Nuratikah; Tarsik, Nor Famiza; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2019)
Not able to borrow books on time? Book doesn't enough? Don’t worry, with Decoded, you will no longer have to go through shelves and disappointed by unavailability of the materials in the library. Combine with cloud library and QR code, simply scan it and voila; everyone able to access Decoded. Decoded is a software that provides thousands of academic material as an alternative to the library. No wait time… simply with a simple scan, you able to access electronic academic materials with ease anytime and anywhere you want available on database cloud. Through this software, the library can prolong the lifespan of the materials while also saving space for a new publication. Information will be available for the student without the hassle and saving so much time.